2018
DOI: 10.1093/mnras/sty3053
|View full text |Cite
|
Sign up to set email alerts
|

The RMS survey: Ammonia mapping of the environment of young massive stellar objects – II★

Abstract: We present the results from NH 3 mapping observations towards 34 regions identified by the Red MSX Source (RMS) survey. We have used the Australia Telescope Compact Array to map ammonia (1,1) and (2,2) inversion emission spectra at a resolution of 10 with velocity channel resolution of 0.4 km s −1 towards the positions of embedded massive star formation. Complementary data have been used from the ATLASGAL and GLIMPSE Legacy Surveys in order to improve the understanding of the regions and to estimate physical p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…This suggests that embedded compact HII regions are having an impact on the physical conditions of the surrounding molecular gas. This feature of temperature distribution is also seen in some IRDCs, MYSOs and HII regions (Urquhart et al 2015;Billington et al 2019). Previous studies measuring molecular gas temperature have reported that quiescent regions exhibit temperatures of 10 -15 K, while active starforming regions associated with massive young stellar objects and HII regions show temperatures higher than 20 K (e.g.…”
Section: Star Formation Feedback Traced By Gas Temperaturementioning
confidence: 58%
See 3 more Smart Citations
“…This suggests that embedded compact HII regions are having an impact on the physical conditions of the surrounding molecular gas. This feature of temperature distribution is also seen in some IRDCs, MYSOs and HII regions (Urquhart et al 2015;Billington et al 2019). Previous studies measuring molecular gas temperature have reported that quiescent regions exhibit temperatures of 10 -15 K, while active starforming regions associated with massive young stellar objects and HII regions show temperatures higher than 20 K (e.g.…”
Section: Star Formation Feedback Traced By Gas Temperaturementioning
confidence: 58%
“…Previous studies measuring molecular gas temperature have reported that quiescent regions exhibit temperatures of 10 -15 K, while active starforming regions associated with massive young stellar objects and HII regions show temperatures higher than 20 K (e.g. Urquhart et al 2015;Friesen et al 2017;Hogge et al 2018;Billington et al 2019;Keown et al 2019). In this study, the observation points that measured temperatures higher than 20 K are defined as the region under the influence of star-formation feedback.…”
Section: Star Formation Feedback Traced By Gas Temperaturementioning
confidence: 61%
See 2 more Smart Citations
“…Recently, high-resolution (∼ 0.1 pc scale) observations of dense cores in giant molecular clouds were carried out using radio interferometers (e.g., Billington et al 2019), whereas large-scale NH 3 mapping observations (∼ 10 pc scale) aiming to investigate the impact of stellar feedback and interactions in high-mass star formation remain limited. Sh 2-255 and Sh 2-257 are ideal for studying the interaction between H II regions and molecular clouds.…”
Section: Introductionmentioning
confidence: 99%